Conflicts and Islah Strategy of Muslim Women Organization: Case Study of ‘Aisyiyah in Intra and Inter-Organizational Divergence - Siti Syamsiyatun (Al-Jami'ah Research Centre, 2020)
Indonesians have witnessed the rise and fall of women organizations, at both micro and macro levels. In 1928, there were at least thirty women’s organizations from various religious and regional backgrounds, and working on various issues, succeeded in holding the first Indonesian Women’s Congress. But a century later there were only three organizations that survived, one of them is ‘Aisyiyah. This current paper aims at exploring factors that contribute to the survival of the organization from a perspective of conflict resolution; it investigates what strategies they use to address intra and inter-organizational conflicts, by employing a qualitative analytical approach by way of the case study. The data were collected through interviews and documentation. From studying several cases of organizational conflicts encountered by ‘Aisyiyah at different times it is found that the organization constantly encounters intra and inter-organizational conflicts. It applies various strategies to deal with them in accordance with the situation and necessity. What is pivotal is ‘Aisyiyah’s willingness to explore possibilities to find win-win solutions, such as silence, inaction, negotiation, mediation to conflict transformation, to find islah ways. However, when foundational values are at stake, ‘Aisyiyah would not be reluctant to contend and use the strategy of threat.[Bangsa Indonesia telah menjadi saksi bermunculan dan berjatuhannya organisasi perempuan, baik tingkat nasional maupun lokal. Di tahun 1928 terdapat kurang lebih 30 organisasi perempuan yang terlibat aktif dalam Kongres Perempuan Indonesia pertama. Namun seabad kemudian hanya tersisa tiga organisasi yang bertahan, salah satunya 'Aisyiyah. Dengan pendekatan resolusi konflik, artikel ini menjelaskan faktor dan strategi pendukung untuk bertahan menghadapi ketegangan internal dan eksternal organisasi. Data yang dikumpulkan melalui wawancara dan studi arsip menunjukkan bahwa 'Aisyiyah dalam beberapa periode yang berbeda telah menghadapi persoalan di dalam dan antar organisasi yang mana membutuhkan strategi yang tepat dalam penyelesaiannya. Terpenting bagi 'Aisyiyah adalah usaha mencari solusi yang sama-sama menguntungkan menuju jalan damai seperti mendiamkan, negosiasi, mediasi hingga transformasi konflik. Namun jika nilai-nilai dasar organisasi menjadi taruhan, 'Aisyiyah tentu tak segan mengambil langkah tegas].